Documents and discussions. Suppl. for record purposes to International Information, publ. by the Secretariat of the Labour and Socialist International (L.S.I.)
Suppl. to: International Information (ZK 16049) - German ed.: Dokumente und Diskussionen (ZK 16050) - French ed.: Documents et discusions (ZK 16048).